Efektivitas Penyuluhan Terhadap Tingkat Pengetahuan Kontrasepsi IUD Pada Wanita Usia Subur - Atik Ismiyati (Jurnal Ilmu Kebidanan (Journal of Midwivery Science), 2018)
Background: Family planning is a direct effort aimed at reducing birth rates. The majority of acceptors use injectingcontraception, whereas IUD acceptors are in the umpteenth order, whereas in terms of the various things actually IUD contraceptive devices are much more profitable. There are many things that influence the acceptors inchoosing contraceptives include the level of knowledge, the number of children, and the behavior of mother usingcontraception.Objective: To identify the level of knowledge about IUD contraception in women.Research Method: Quasi experiment with Non-Equivalent Control Group with “one group pretest-posttest design”design. The population of all women are married. Sampling technique using purposive sampling. Data collectionusing questionnaires with closed question types. The questionnaire was distributed to the respondents before thecounseling and a month after the counseling.Result: Based on statistical test show p = 0,000; p-value <0.05 means that counseling can increase the level ofknowledge about IUD contraception in women.Conclusion: Counseling about IUD contraception effectively improves knowledge of IUD contraceptives.Keywords: Knowledge, IUD Contraception